Heterogeneous (mis-) perceptions of energy costs: Implications for measurement and policy design - Sébastien Houde; Erica Myers (ETH Zurich, CER-ETH - Center of Economic Research, 2019)
Quantifying heterogeneity in consumers' misperceptions of product costs is crucial for policy design. We illustrate this point in the energy context and the design of Pigouvian policies. We estimate non-parametric distributions of perceptions of energy costs in the U.S. appliance market using a revealed preference approach. We show that the average degree of misperception is misleading - while the largest share of consumers correctly perceives energy costs, a significant share undervalues them, and smaller shares either significantly overvalues or completely ignores them. We show that setting a tax based on mean misperception deviates substantially from the optimal tax that accounts for heterogeneous misperceptions. While correctly characterizing misperception is crucial for setting optimal Pigouvian taxes for externalities, it is less important for setting optimal standards. We find that standards can largely outperform taxes. Standards' advantage is they reduce variance in energy operating costs relative to taxes, which internalizes distortionary effects from misperceptions.
Keywords: Q41; Q50; L15; D12; D83; 330; demand estimation; misperceptions; energy efficiency gap; behavioral welfare economics